The Role of Integrating Sustainability Accounting into Financial Reporting: Evidence from Kurdistan Manufacturing Companies - Rebin Bilal Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study aims to explore the roles of the independent variable (integrating sustainability accounting) into the dependent variable (financial reporting) in Kurdistan manufacturing companies and identify possible solutions to these roles. Primary data was collected from 105 sustainability managers, chief executive officers, and chief financial officers of 35 companies drawn from 7 vital industries to the Kurdistan economy. Consequently, a multiple regression model was estimated to determine the impact of each purported role on financial reporting. The results of the study indicated that the Lack of awareness of sustainability accounting, Insufficient data and resources, and adverse perceptions about sustainability accounting undermine manufacturing companies’ financial reporting. The study recommends that company managers prioritize educational and training initiatives aimed at enhancing understanding of sustainability accounting to enhance the effective integration of sustainability accounting in financial reporting. Additionally, the study commands companies to invest in data management processes and systems to enhance the availability and accuracy of sustainability data